Economic Development in Kosovo, The Current Situation - Vlahna, Dafina; Kuçi , Argona; Vlahna, Kastriote (Riviera Publishing, 2023)
The purpose of this research is to understand and analyze the economic development in Kosovo. The research method used in this study is a literature review with a comparative approach. The results of this research indicate that the state of Kosovo, since its establishment as a legal entity, has formulated rules for its optimal functioning and development, with a special focus on the Economic sector. It is not coincidental that a particular emphasis is given to the Economic sector, as a well-developed economy correlates with a advanced nation. First and foremost, the economy is the best reflection of a nation, and through it, one can gauge the financial capacity of a country and the extent to which its workforce is developed. Considering that the economy forms the foundation of a stable and functional state, strategies are devised for its development. This involves analyzing and evaluating all efforts that can influence the country's economic growth. Therefore, the analysis of the economic situation begins at the central level, and then shifts the focus to the local level, determining which cities can contribute more to economic development. Statistical data on the economic conditions at the local level are based on the geographical area and the population of the municipalities. As a result, in terms of population and geographical area, the municipality of Prizren ranks second among municipalities.